A user-friendly software for automated knowledge-based virtual surgical planning in mandibular reconstruction - Hagen, Niclas; Freudlsperger, Christian; Kühle, Reinald; Bouffleur, Frederic; Knaup-Gregori, Petra; Hoffmann, Jürgen; Eisenmann, Urs (Journal of Clinical Medicine, 2025)
Background/Objectives: Virtual surgical planning (VSP) has become the gold standard in mandibular reconstructions with autografts. While commercial services are available, efforts are under way to address their shortcomings, which may include inefficiency, inconvenience, and susceptibility to error. We developed a novel approach to calculate knowledge-based reconstruction proposals. The objective of our work is to implement software for automated VSP and to evaluate it on retrospective clinical cases. Methods: We developed software, which incorporates registration of a naturally shaped mandible, tumor resection planning, knowledge-based calculation of reconstruction proposals, and manual refinement of proposals. Three surgeons planned 21 retrospective clinical cases utilizing our software. They rated its usability via the System Usability Scale (SUS) and rated the quality of the proposed reconstructions and the final surgical plan via a five-point Likert scale (1: totally disagree-5: totally agree). Results: Surgeons rated the usability with an average SUS score of 76.7. Times for VSP were consistently less than 20 min. The surgeons agreed with the proposals with a mean value of 4.7 ± 0.4. In 15 cases they made minor refinements. Finally, they agreed with the final surgical plan in twenty cases (score of 5) and with minor discrepancies in one case (score of 4). Conclusions: We developed an easy-to-use software for the automated VSP of mandibular reconstructions with autografts. The results demonstrate that reconstruction proposals can be calculated efficiently based on standardized rules. Our system allows surgeons to autonomously derive, compare, and rapidly refine high-quality reconstruction proposals based on key decisions.